Mad Dogs and Meerkats : a History of Resurgent Rabies in Southern Africa - Brown, Karen, 1964- (Ohio University Press series in ecology and history., 2011)
"In Mad dogs and meerkats, Karen Brown links the increase of rabies in Southern Africa to the HIV/AIDS epidemic. Her study shows that the most afflicted regions of South Africa have seen a dangerous rise in feral dog populations as people lack the education, means, or will to care for their pets or take them to inoculation centers. Ineffective disease control, which in part depends on management policies in neighboring states, has exacerbated the problem. The book traces the history of rabies in South Africa and neighboring states from 1800 to the present and shows how environmental and economic changes brought about by European colonialism and global trade have had long-term effects"--Provided by publisher.